Analysis of the Implementation of the Halal Value Chain in MSMEs as an Effort to Strengthen the Halal Industry Ecosystem in Purwodadi District, Pasuruan Regency. - Nadia Ibrahim; Aslikhah; Sukamto (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze implementation of the halal value chain among MSMEs in Purwodadi District, including the level of understanding and awareness of business actors, the challenges encountered, and efforts to optimize the strengthening of the halal industry ecosystem. This study employs a descriptive qualitative approach. Data collection was carried out through in-depth interviews, observation, and documentation involving ten MSME actors. The data were subsequently analyzed using data reduction, data display, and conclusion-drawing techniques. The findings indicate that the implementation of the halal value chain has been carried out within the framework of national regulations and supported by halal certification policies; however, it is not yet fully integrated. The understanding and awareness of MSME actors vary, where some have implemented halal principles comprehensively, while others are still limited to basic aspects such as hygiene and product safety. The implementation across value chain stages also shows varying levels of application. The main challenges include limited digital literacy, insufficient understanding of the halal concept, uneven halal certification ownership, limited mentoring support, and suboptimal utilization of digital marketing. Optimization efforts are needed through improving digital literacy, strengthening halal understanding, enhancing mentoring programs, and developing digital-based marketing to ensure a more effective and sustainable implementation of the halal value chain.